Uncovering the Promotion of CeO2/CoS1.97 Heterostructure with Specific Spatial Architectures on Oxygen Evolution Reaction. Issue 42 (3rd September 2021) - Dai, Tengyuan; Zhang, Xin; Sun, Mingzi; Huang, Bolong; Zhang, Nan; Da, Pengfei; Yang, Rui; He, Zidong; Wang, Wei; Xi, Pinxian; Yan, Chun‐Hua
Abstract: Structural engineering and compositional controlling are extensively applied in rationally designing and fabricating advanced freestanding electrocatalysts. The key relationship between the spatial distribution of components and enhanced electrocatalysis performance still needs further elaborate elucidation. Here, CeO2 substrate supported CoS1.97 (CeO2 ‐CoS1.97 ) and CoS1.97 with CeO2 surface decorated (CoS1.97 ‐CeO2 ) materials are constructed to comprehensively investigate the origin of spatial architectures for the oxygen evolution reaction (OER). CeO2 ‐CoS1.97 exhibits a low overpotential of 264 mV at 10 mA cm −2 due to the stable heterostructure and faster mass transfer. Meanwhile, CoS1.97 ‐CeO2 has a smaller Tafel slope of 49 mV dec −1 through enhanced adsorption of OH −, fast electron transfer, and in situ formation of Co(IV)O2 species under the OER condition. Furthermore, operando spectroscopic characterizations combined with theoretical calculations demonstrate that spatial architectures play a distinguished role in modulating the electronic structure and promoting the reconstruction from sulfide to oxyhydroxide toward higher chemical valence. The findings highlight spatial architectures and surface reconstruction in designing advanced electrocatalytic materials. Abstract : Two novel CeO2 /CoS1.97 heterostructure electrocatalysts (CeO2 ‐CoS1.97 and CoS1.97 ‐CeO2 ) are constructed to investigate the relationships between spatial architectures and oxygen evolution reaction (OER) performances, where different configuration endows hybrids with distinct intermediate adsorption, modulated electronic structures, and promoted electrochemical reconstruction, thus improving the OER kinetics and performances. This work sheds light on the importance of rational design and synthesis of advanced hybrid electrocatalysts with functional spatial architectures.